2021
DOI: 10.1332/204674319x15761552010506
|View full text |Cite
|
Sign up to set email alerts
|

When equal partners become unequal parents: couple relationships and intensive parenting culture

Abstract: Based on longitudinal research with (heterosexual) couples in the UK, this article tracks their experiences of becoming parents for the first time. The suggestion is that new parents are caught in an uncomfortable confluence between competing discourses around ideal relationships and those around ideal parenting. On the one hand, they must be committed to egalitarian ideals about the division of care. On the other, they must be parenting ‘intensively’, in ways which are markedly more demanding for mothers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
0
26
0
1
Order By: Relevance
“…Fathers meanwhile report being primarily judged by their breadwinning ability, and report facing extra barriers to work-family integration policies (Gatrell, Burnett, Cooper, & Sparrow, 2015). Even when fathers want to be more involved in a handson way, it is may be easier to 'fall back' into traditional roles (Miller, 2011, Faircloth 2020). Nonetheless, overall, women in this study displayed little guilt in transferring their leave, while most of the men showed a reluctance to take leave from work.…”
Section: Interplay Between Social Context and Negotiationsmentioning
confidence: 99%
“…Fathers meanwhile report being primarily judged by their breadwinning ability, and report facing extra barriers to work-family integration policies (Gatrell, Burnett, Cooper, & Sparrow, 2015). Even when fathers want to be more involved in a handson way, it is may be easier to 'fall back' into traditional roles (Miller, 2011, Faircloth 2020). Nonetheless, overall, women in this study displayed little guilt in transferring their leave, while most of the men showed a reluctance to take leave from work.…”
Section: Interplay Between Social Context and Negotiationsmentioning
confidence: 99%
“…While the study was open to any parent or caregiver of children who attended primary school in Victoria to maximise the participant variation, the researchers were only contacted by mothers. This was expected as current literature suggests child feeding is considered a primary role of the mother 11,15 …”
Section: Methodsmentioning
confidence: 80%
“…This is in contrast to mothers, who are expected to focus on the "caring for" responsibilities, which includes child nutrition and is still viewed as one of the most critical aspects of motherhood. Current literature suggests that health promotion interventions seeking to improve children's dietary intake are primarily focused on mothers, 11,15 which reinforce gendered expectations. School lunchboxes can be considered a public example of good mothering.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisas existentes têm indicado que, comparativamente com as mães, os pais de crianças com desenvolvimento atípico são menos envolvidos nos cuidados diários com as crianças e, consequentemente, apresentam melhores níveis de saúde mental 10 . Portanto, as cargas mental e física 42 que recaem mais fortemente sobre as mães acabam por reduzir sua saúde mental e satisfação com a vida.…”
Section: Discussionunclassified